COVID-19 vaccine – technical aspects of vaccination - Jaciubek, Marzena; Prasek, Karolina (Nursing in the 21st Century, 2021)
COVID-19 VACCINE - TECHNICAL ASPECTS OF VACCINATION Introduction. All over the world the fight against the SARS-CoV-2 virus, which causes COVID-19, has already begun. Very quick development and testing of medicinal preparations with such a high efficiency (94-95%), which can be administered to adult patients for mass immunization, makes this fight possible. The production and delivery of a huge number of vaccines remains a challenge, but an undoubtedly important aspect is the safe and compliant administration of medicinal preparations. People currently authorized to administer COVID-19 vaccines are doctors, paramedics, nurses, midwives, and school hygienists. However, there is a lot of conflicting information on how to administer the COVID-19 vaccine. Conclusion. Nurses have administered vaccination since many years, having proper education and experience. Nowadays available vaccines against COVID-19 are administered intramuscularly into the deltoid muscle. The recommendations say that administering of the vaccine must be performed with 90 degrees to the surface of the skin simultaneously stretching the skin with index finger and thumb, without aspiration after injection. This article presents basic information about the vaccine and the algorithm for administering the COVID-19 vaccine developed by the authors.